Analysis of Situation and Pattern of Diseases of the Neonates Admitted in Department of Pediatric Surgery of a Medical College Hospital - Mostaque, AK; Hossain, Sayed Zahid (Journal of Surgical Sciences, 2020)
Background: Neonatal surgery (NS) is an extremely challenging leading edge of pediatric surgery. In our country NS death were 8% due to treatable congenital anomalies. The objectives of study were to observe yearly admission of NS patients, age of presentation, anthropometric records, prenatal record and types of congenital anomalies, and mortality of treated neonates. Materials and Methods: This cross-sectional study was conducted on 337 admitted neonates to assess the state of 70 consecutive NS patients admitted in the Pediatric Surgery ward. Birth weight was compared with randomly selected and sex matched 154 were neonatology neonates (NN), and 113 delivered un-admitted healthy neonates of the labor-ward (LN). The variables observed were number of neonatal surgical patients admitted, age of presentation, birth and admission weight, prenatal ultrasonogram for fetal anomalies and the types of anomalies, outcome (mortality) of neonatal surgery. Results: The mean age of surgical neonates at the time of admission was 5.7 ± 6.39 (1-25) days. Mean birth weight of surgical and neonatology neonates was 2.66 ± 0.76 (1.5-4.5) kg and 2.24 ± 0.71 (0.9-4) kg respectively. The difference was significant (p < 0.01). The mean admission weight of the surgical and neonatology neonates were 2.57 ± 0.66 (1.4-4.1) kg and 2.25 ± 0.62 (0.8-4.1) kg respectively showing significant difference (p < 0.01). Ten percent of NS patients and 38.3% of NN patients had records of prenatal ultrasonogram, and their reports were normal fetus. The difference was significant (Z = 4.36). Eighty seven percent NS patients and 49% NNs were delivered at home and the difference was significant (Z = 4.49). Major surgical problem were anorectal malformation (48.6%) and neonatal intestinal obstruction (20%). The treatments given to the patient admitted in the pediatric surgery ward were emergency laparotomy with resection-anastomosis, ileostomy, and transverse loop colostomy in 29 (41.3%), anoplasty 21 (30%), incision and drainage of abscess 5 (7.1%), and conservative treatment 15 (21.43%). The mortality rate of neonatal surgical and neonatology patients was 12.9% and 13% respectively. Conclusion: The number of NS patients (work load) indicated the necessity of establishment of a NS unit which could be viable. The mortality of NS patients were due to low birth weight, and delivery at home causing transport delay from birth place to the pediatric surgery ward because of lack of prenatal awareness of presence of congenital anomalies. Anorectal malformation is the commonest congenital anomaly, followed by neonatal intestinal obstruction. Emergency laparotomy was the major surgical intervention offered. To improve the survival of the NS patients, prenatal diagnosis of the congenital anomaly, mandatory delivery at defined hospital, rapid transport of the surgical neonates born away from hospital, and establishment of a NS unit in tertiary level hospitals were indicated. Journal of Surgical Sciences (2020) Vol. 24 (1) : 26-31